Investigation of High School 12th Grade Students' Attitudes Towards the Topic of Derivatives - Büşra Ateş; Neşe Dokumacı Sütçü (Yaşadıkça Eğitim)
The aim of this study is to examine the attitudes of 12th-grade high school students towards the topic of derivatives. This research, which is descriptive and correlational in nature, involved 223 students. A personal information form and an Attitude Scale Toward the Topic of Derivatives were employed as data collection tools. A second-order confirmatory factor analysis was conducted to validate the three-factor structure of the Attitude Scale Toward the Topic of Derivatives, developed by Kara and Yalçınkaya (2017) for pre-service teachers, for adaption to 12th-grade high school students. Descriptive statistics, independent samples t-test, Pearson, and Spearman-Brown Correlation Coefficient were utilized in data analysis. The study found that students' attitudes toward the behavioral, cognitive, and problem-solving dimensions of the scale were at a moderate levels and did not show a statistically significant difference based on gender. It was determined that Anatolian High School students exhibited significantly higher attitudes toward the behavioral and problem-solving dimensions compared to Imam Hatip High School students. Science track students demonstrated significantly higher attitudes toward each dimension compared to equal weight track students. Additionally, students who participated courses/tutoring centers demonstrated significantly higher attitudes toward the behavioral dimension than those who did not. On the other hand, the study revealed a moderate, positive, and statistically significant relationship between students' first-term mathematics grades, their level of liking mathematics, and their weekly study hours on derivatives, and their attitudes toward the behavioral and problem-solving dimensions. A low, positive, and statistically significant relationship was found between these factors and attitudes toward the cognitive dimension.